PENGARUH LATIHAN MENGGUNAKAN RESISTEN BAND DAN MEDICINE BALL TERHADAP KEMAMPUAN SMASH PADA KEGIATAN EKSTRAKURIKULER BOLA VOLI SISWA SMA FRATER PALOPO - Jerni; Riswanto, Heri; Ahmad; Hidayat, Rachmat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of training using resistance bands and medicine balls on the smash ability of volleyball extracurricular students at SMA Frater Palopo. The research was conducted from May to June 2025 at SMA Frater, located in Palopo City, South Sulawesi Province. The research method used was an experimental method with a two-group pretest-posttest design. The sample consisted of 20 students divided into two groups: Group A used resistance band training and Group B used medicine ball training, with a total of 16 treatment sessions. The instrument used was a smash test with five target attempts. The data analysis results showed that both types of training had a significant effect on improving smash ability. Based on the paired sample t-test, a significant value (p < 0.05) was obtained in both groups. Furthermore, the results of the independent sample t-test showed no significant difference between Group A and Group B (p = 0.067). Therefore, it can be concluded that resistance band training and medicine ball training do not have a significant difference in improving the smash ability of volleyball extracurricular students.